2018
DOI: 10.1038/s41467-018-05427-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nine new susceptibility loci for endometrial cancer

Abstract: Endometrial cancer is the most commonly diagnosed cancer of the female reproductive tract in developed countries. Through genome-wide association studies (GWAS), we have previously identified eight risk loci for endometrial cancer. Here, we present an expanded meta-analysis of 12,906 endometrial cancer cases and 108,979 controls (including new genotype data for 5624 cases) and identify nine novel genome-wide significant loci, including a locus on 12q24.12 previously identified by meta-GWAS of endometrial and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
266
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 203 publications
(275 citation statements)
references
References 59 publications
(83 reference statements)
3
266
1
2
Order By: Relevance
“…Summary statistics for the ovarian cancer analysis were from GWAS studies of 25,509 ovarian cancer cases and 48,941 controls conducted by the Ovarian Cancer Association Consortium (OCAC) 82 . The endometrial cancer results were from GWAS studies of 12,906 endometrial cancer cases and 108,979 controls from the Endometrial Cancer Association Consortium (ECAC) 83 . In addition, MRs for breast and ovarian cancer risk specifically in carriers of a BRCA1 or a BRCA2 mutation were carried out using results from GWAS studies conducted by the CIMBA consortium 81,82 .…”
Section: Integration With Cancer Data and Modelling Loy As A Causal Ementioning
confidence: 99%
“…Summary statistics for the ovarian cancer analysis were from GWAS studies of 25,509 ovarian cancer cases and 48,941 controls conducted by the Ovarian Cancer Association Consortium (OCAC) 82 . The endometrial cancer results were from GWAS studies of 12,906 endometrial cancer cases and 108,979 controls from the Endometrial Cancer Association Consortium (ECAC) 83 . In addition, MRs for breast and ovarian cancer risk specifically in carriers of a BRCA1 or a BRCA2 mutation were carried out using results from GWAS studies conducted by the CIMBA consortium 81,82 .…”
Section: Integration With Cancer Data and Modelling Loy As A Causal Ementioning
confidence: 99%
“…the lead variant and other correlated variants) at these loci are non-coding and likely mediate their effects through gene regulation (as reviewed in [4]). Indeed, we previously found that a majority of endometrial cancer risk CVs from ten recently discovered GWAS loci were coincident with promoter-or enhancer-associated epigenetic features in relevant cell lines or tissues [1]. Notably, the overlap between CVs and these elements was significantly greater for features observed in endometrial cancer cell lines after stimulation with estrogen [1], one of the most established risk factors for endometrial cancer [5][6][7].…”
Section: Introductionmentioning
confidence: 92%
“…To determine if promoter-associated HiChIP loops (i.e. those potentially involved with gene regulation) are enriched for heritability of endometrial cancer at a genome-wide level, we applied stratified linkage disequilibrium (LD) score regression analysis to the GWAS summary statistics from the largest study of endometrial cancer performed to date [1]. All four endometrial cell lines demonstrated an enrichment of endometrial cancer heritability in the anchors of promoterassociated loops ( Table 2), although the enrichment in Ishikawa did not reach statistical significance (Bonferroni threshold, p <0.0125).…”
Section: Hichip Promoter Loops Are Enriched For Endometrial Cancer Hementioning
confidence: 99%
See 2 more Smart Citations